If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -6(2 + 3p) = -87 3p + (2 * -6 + 3p * -6) = -87 3p + (-12 + -18p) = -87 Reorder the terms: -12 + 3p + -18p = -87 Combine like terms: 3p + -18p = -15p -12 + -15p = -87 Solving -12 + -15p = -87 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -15p = -87 + 12 Combine like terms: -12 + 12 = 0 0 + -15p = -87 + 12 -15p = -87 + 12 Combine like terms: -87 + 12 = -75 -15p = -75 Divide each side by '-15'. p = 5 Simplifying p = 5
| (-25+50)-(-4-6)= | | R-6=-r | | 9+5j=2j | | 50=7d+1 | | -6y=27 | | 4-27x=0 | | 2/3x+5=7-1/3x | | 14x-13x+10=5 | | 11+-1(3x-6)+2(4x+5)-x= | | a=4c | | -1-4c=-6-9c | | 4m=3m+7 | | 3/5-3/4x=1/2 | | -5c=4-c | | 6+4(1.4)=-10(1.4)+26 | | 15y+10=16 | | 9+5d=6d | | (3-7)-(9-12)= | | s+31/2s+10=46 | | X+3x=19 | | 40=3t-11t | | -9z-9=-10z | | (-15-15)-(15-13)= | | 17/30-1/6 | | 6b=7b+6 | | 1/3(9+6x) | | 13/20-1/2 | | 7m^2-38m+15=0 | | -k=-10+4k | | 4a^2-4a-1=0 | | 1,512.50/27= | | 2y+0y=10 |